2022
DOI: 10.3390/life12071042
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Associations between Functional Capacity, Cognitive Function and Well-Being in Older Adults

Abstract: Background: The present study aimed to explore the associations between functional capacity and global cognition, executive function and well-being in older adults. Methods: Ninety-seven older adults (age 80.6 ± 8.2 years) were examined for global cognitive function (Mini-Mental State Examination), executive function (symbol cancellation test), functional capacity (sit-to-stand tests, 6 min walk test, timed up-and-go test and handgrip strength test) and well-being (quality of life, fatigue levels, sleep qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 83 publications
0
9
0
1
Order By: Relevance
“…Other potential factors may also affect PC, PB, and PAQ, e.g., perception of comfort and breathability may vary according to age, as younger individuals have more residual lung volume and lung capacities than elder adults [40]. For perceiving comfort and breathability, all individuals should have the same or a similar functional capacity of the parietal cortex which is an area of the brain responsible for sensory perception and integration, including the management of taste, hearing, sight, touch, and smell [41]. Its functional capacity changes due to age [41].…”
Section: Limitations and Future Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Other potential factors may also affect PC, PB, and PAQ, e.g., perception of comfort and breathability may vary according to age, as younger individuals have more residual lung volume and lung capacities than elder adults [40]. For perceiving comfort and breathability, all individuals should have the same or a similar functional capacity of the parietal cortex which is an area of the brain responsible for sensory perception and integration, including the management of taste, hearing, sight, touch, and smell [41]. Its functional capacity changes due to age [41].…”
Section: Limitations and Future Studymentioning
confidence: 99%
“…For perceiving comfort and breathability, all individuals should have the same or a similar functional capacity of the parietal cortex which is an area of the brain responsible for sensory perception and integration, including the management of taste, hearing, sight, touch, and smell [41]. Its functional capacity changes due to age [41]. Perception is also strongly influenced by gender [42].…”
Section: Limitations and Future Studymentioning
confidence: 99%
“…It was found that there is a gradual increase of fall by 35% to 40% after the age of 60 years ( World Health Organization, 2007 ). Physical activity enhances balance and strength of the older adults resulting in the prevention of falls and improving physical function and quality of life of the older adults ( Ferreira et al, 2012 ; Stavrinou et al, 2022 ; Wannamethee & Atkins, 2019 ; World Health Organization, 2007 ). Studies on improving balance, strength and endurance ( Bootsman et al, 2018 ; Ferreira et al., 2012 ; Zouita et al., 2020 ), relieving pain and enhancing functional mobility ( Tse et al, 2011 , 2013 ), and preventing frailty ( Mesquita et al, 2015 ; Trombetti et al., 2016 ) in old age have shown that physical activity is positively associated with functional health.…”
Section: Introductionmentioning
confidence: 99%
“…Population aging is a worldwide phenomenon; the global share of older adults (aged 60 years or over) increased from 9.2% in 1990 to 11.7% in 2013 and will continue to grow, reaching to 21.1% by 2050 (United Nations, 2022). Physical activity is considered as a key to successful and healthy aging (Hallal et al, 2012; World Health Organization, 2022) because regular physical activity plays a significant role in enhancing physical fitness, functional ability and quality of life in old age (Blewitt & Chockalingam, 2017; Stavrinou et al, 2022; Tyndall et al, 2018). Age-related physical decline and corresponding loss of functional capacity are related to the loss of muscle mass (sarcopenia), decrease of aerobic capacity and joint range motion, changes in the sensory system, and consequently would reduce mobility and fitness (Elam et al, 2021; Nelson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…While aerobic exercise plus resistance training improved physical function and balance, leading to improved quality of life [20], 6-month aerobic exercise also improved cognitive function in older adults with MCI [21]. Greater levels of physical function (mobility, exibility, and grip strength) were associated with better cognitive and executive function performance and improved quality of life in older adults [22]. The association of physical and cognitive function should be considered when designing lifestyle interventions to improve QOL in this population.…”
Section: Introductionmentioning
confidence: 99%